FAKTOR PENDUKUNG DAN PENGHAMBAT INOVASI PEMANFAATAN SEKAM PADI SEBAGAI BIOENERGI ALTERNATIF PADA KELOMPOK TANI PADI SAWAH DI DESA AMBOPI KECAMATAN TONGAUNA UTARA KABUPATEN KONAWE - Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
Rice husk utilization as an alternative bioenergy source has emerged as a promising innovation to promote renewable energy development while enhancing the economic value of agricultural waste. However, the successful adoption of this innovation depends not only on the availability of appropriate technology but also on various supporting and inhibiting factors that influence its implementation among farmers. This study aimed to analyze the supporting and inhibiting factors affecting the innovation of rice husk utilization as an alternative bioenergy source among paddy farmer groups in Ambopi Village, North Tongauna District, Konawe Regency, Indonesia. A qualitative approach with a case study design was employed. The study involved 17 members of the Sido Makmur Farmer Group, selected using a census technique. Data were collected through field observations, in-depth semi-structured interviews, and documentation, while data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing and verification. Data credibility was ensured through source and method triangulation. The findings revealed that the innovation was supported primarily by the abundant availability of rice husk as a renewable biomass resource and by farmers' openness to adopting beneficial agricultural innovations. These factors provide favorable conditions for developing community-based bioenergy using locally available resources. Conversely, limited government policies and extension support, together with inadequate technological knowledge and skills, were identified as the major barriers that constrained the adoption process. From the perspective of Rogers' Diffusion of Innovation Theory, the development of rice husk-based bioenergy is influenced by the interaction between local resource availability, farmers' human capacity, institutional support, and access to appropriate technology. This study contributes to the literature by demonstrating that successful bioenergy innovation requires an integrated innovation ecosystem involving farmers, agricultural extension agents, local governments, and higher education institutions through continuous capacity building, technology transfer, technical assistance, and supportive public policies. Strengthening these components is essential for accelerating innovation adoption and promoting sustainable agricultural waste management in rural communities.